Prevalence of Listeria monocytogenes in Raw Meats Marketed in Bangkok and Characterization of the Isolates by Phenotypic and Molecular Methods (Journal of Health, Population and Nutrition, 2011)
Listeria monocytogenes causes listeriosis characterized by septicaemia, encephalitis, and abortion or stillbirth. Regular monitoring of its prevalence in food and characterization of its phenotypes and genotypes are necessary for disease surveillance and tracing the epidemic outbreaks. In this study, the prevalence of L. monocytogenes in raw meats marketed in Bangkok was 15.4%. The bacteria isolated from meat were serotyped and genotyped using enterobacterial repetitive intergenic consensus–polymerase chain reaction (ERIC-PCR). Their virulence-associated genes, antimicrobial susceptibility, and ability to invade intestinal epithelial cells were studied. All 22 L. monocytogenes strains isolated from 104 raw meat samples carried virulence-associated genes, such as actA, flaA, hlyA, iap, inlA, inlB, and prfA. These were serotype 4b, suggesting their pathogenic and epidemic potential. These isolates could be classified into six ERIC-PCR groups: A-F. The majority (59.1%) of the isolates belonged to Group A, and three isolates were Group D which was closely related to the Group A. Two isolates each were Group C and E, and one isolate each was group B and F. Although the isolates belonged to the same serotype and genotype and were all equipped with the virulence-associated genes, they showed a different cell invasion capability and antibiotic susceptibility. All the isolates were susceptible to ampicillin, amikacin, chloramphenicol, gentamicin, imipenem, penicillin G, sulphamethoxazole-trimethoprim, and tetracycline. However, one isolate showed only intermediate susceptibility to tetracycline. The data provide the first molecular insight into the L. monocytogenes isolates in Thailand and elucidate a potential risk of people contracting listeriosis. Key words: Characterization; Phenotype; Flagellin; Genes typing; Haemolysin; Internalins; Invasins; Listeria monocytogenes; Listeriolysin; Listeriosis; Microbial sensitivity tests; Virulence genes; ThailandDOI: 10.3329/jhpn.v29i1.7565J HEALTH POPUL NUTR 2011 Feb;29(1):26-38